Beyond conflict: exploring the spectrum of human–wildlife interactions and their underlying mechanisms - Bhatia, Saloni; Redpath, Stephen Mark; Suryawanshi, Kulbhushansingh; Mishra, Charudutt (Oryx, 2020)
Humans have lived alongside and interacted with wild animals throughout evolutionary history. Even though wild animals can damage property, or injure humans and domesticated animals, not all interactions between humans and wildlife are negative. Yet, research has tended to focus disproportionately on negative interactions leading to negative outcomes, labelling this human–wildlife conflict. Studies have identified several factors, ranging from gender, religion, socio-economics and literacy, which influence people's responses to wildlife. We used the ISI Web of Knowledge database to assess quantitatively how human–wildlife interactions are framed in the scientific literature and to understand the hypotheses that have been invoked to explain these. We found that the predominant focus of research was on human–wildlife conflict (71%), with little coverage of coexistence (2%) or neutral interactions (8%). We suggest that such a framing is problematic as it can lead to biases in conservation planning by failing to consider the nuances of people's relationships with wildlife and the opportunities that exist for conservation. We propose a typology of human responses to wildlife impacts, ranging from negative to positive, to help moderate the disproportionate focus on conflict. We suggest that standardizing terminology and considering interactions beyond those that are negative can lead to a more nuanced understanding of human–wildlife relations and help promote greater coexistence between people and wildlife. We also list the various influential factors that are reported to shape human–wildlife interactions and, to generate further hypotheses and research, classify them into 55 proximate (correlates) and five ultimate (mechanisms) factors.